2022
DOI: 10.1007/s10570-022-04570-1
|View full text |Cite
|
Sign up to set email alerts
|

Antibacterial and wound healing properties of cellulose acetate electrospun nanofibers loaded with bioactive glass nanoparticles; in-vivo study

Abstract: Bioactive glasses (BGs) have gained great attention owing to their versatile biological properties. Combining BG nanoparticles (BGNPs) with polymeric nanofibers produced nanocomposites of great performance in various biomedical applications especially in regenerative medicine. In this study, a novel nanocomposite nanofibrous system was developed and optimized from cellulose acetate (CA) electrospun nanofibers containing different concentrations of BGNPs. Morphology, IR and elemental analysis of the prepared el… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 55 publications
0
10
0
1
Order By: Relevance
“…In vitro tests based on human keratinocytes (HaCaT cells) and HDFs confirmed that the nanofibrous system can be potentially applied as a wound dressing material [ 99 ]. BG nanoparticles have also been employed to reinforce cellulose acetate nanofibers (100–200 nm in diameter) to develop a broad spectrum antibacterial wound dressing material that accelerates wound healing [ 118 ]. Another polysaccharide that has been widely studied for biomedical applications is chitosan.…”
Section: Reviewmentioning
confidence: 99%
“…In vitro tests based on human keratinocytes (HaCaT cells) and HDFs confirmed that the nanofibrous system can be potentially applied as a wound dressing material [ 99 ]. BG nanoparticles have also been employed to reinforce cellulose acetate nanofibers (100–200 nm in diameter) to develop a broad spectrum antibacterial wound dressing material that accelerates wound healing [ 118 ]. Another polysaccharide that has been widely studied for biomedical applications is chitosan.…”
Section: Reviewmentioning
confidence: 99%
“…The addition of 58S BG further improved the hydrophilicity of PHB/PCL membranes, which improved cell adhesion, cell proliferation, and biocompatibility. Similarly, Saraf et al [ 93 ] blended BG NPs along with cellulose acetate to produce organic–inorganic composite nanofibers. Composite scaffolds containing 3% of BG displayed smooth nanofibers.…”
Section: Electrospun Inorganic Nanofibers For Tissue Engineering Appl...mentioning
confidence: 99%
“…An innovative composite nanofiber was developed by combining cellulose acetate with 3 wt% BG nanoparticles in the investigation of Sharaf et al [ 110 ] The electrospun nanofibers were identified as antimicrobial substrates against gram‐negative and gram‐positive bacteria. An in vivo study using a diabetic model of male Sprague Dawley rats (nearly 100–120 g) indicated that throughout the 10th day, the wound had already closed due to the incorporation of BG into the polymeric fiber composition.…”
Section: Bioactive Glass‐containing Composite Fibersmentioning
confidence: 99%